Analisa Sistem Informasi Akuntansi Pembelian Bahan Baku Impor Pada Kawasan Berikat - Widyastuti, Indria (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
The aim of the government to establish Kawasan Berikat (KB) is to increase efficiency by bringing the supply of raw materials to the needs of the domestic industry in a timely manner, as well as the availability of promotional facilities to support its marketing, which in turn is expected to increase the competitiveness of export products in the global market.Companies especially those engaged in manufacturing in carrying out their business activities certainly need raw materials. To get the raw material, the company must get it from another party by making a transaction called purchase. Purchase transactions can be classified into two, namely local purchases and import purchases.The issuance of the Decree of the Director General of Customs and Excise No.431 / BC / 2001 which stipulates the imposition of VAT on capital goods and factory equipment that are directly related to PDKB activities originating from other Indonesian Customs Areas (DPIL).The solution to the problem: the imposition of VAT on the purchase of capital goods from other Indonesian Customs Areas (Domestic) in accordance with the provisions of article 2 paragraph (2) PP No. 33 of 1996 stated that "for the delivery of domestic taxable goods to bonded stockpiling sites facilities are given free of charge VAT & PPnBM.